2014
DOI: 10.3126/ijasbt.v2i1.10001
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Management of Eggplant Fruit and Shoot Borer, Leucinodes orbonalis Guenee (Lepidoptera: Pyralidae)

Abstract: Eggplant (Solanum melongena Linnaeus) is one of the most economically important vegetable of tropics having hot-wet climate. The key pest, eggplant fruit and shoot borer, Leucinodes orbonalis Guenee found to be most destructive and first ranked threat especially in South Asia, hence become hot issue for research in this region. It inflicts sizeable damage up to 80 percent in terms of fruit and content of vitamin-C. This situation refrained the farmers growing eggplant, hence relevant literatures were gleaned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
2
13
0
1
Order By: Relevance
“…At high pest pressure, EFSB damage in the Philippines results in yield loss of up to 80.0% of the crop [ 7 ]. Surveys of eggplant farmers in the major eggplant growing provinces of the Philippines [ 7 – 11 ] revealed that almost all of them use chemical insecticides to control EFSB because other control measures such as manual removal of EFSB-damaged fruits and wilted shoots, use of biological control arthropods and pheromone traps [ 12 ] have proven ineffective, impractical and expensive. Eggplant farmers in the Philippines employ frequent applications (20–72 times for 5–6 months/season) of mixtures of insecticides to control EFSB, which increase production costs and pose risks to human health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…At high pest pressure, EFSB damage in the Philippines results in yield loss of up to 80.0% of the crop [ 7 ]. Surveys of eggplant farmers in the major eggplant growing provinces of the Philippines [ 7 – 11 ] revealed that almost all of them use chemical insecticides to control EFSB because other control measures such as manual removal of EFSB-damaged fruits and wilted shoots, use of biological control arthropods and pheromone traps [ 12 ] have proven ineffective, impractical and expensive. Eggplant farmers in the Philippines employ frequent applications (20–72 times for 5–6 months/season) of mixtures of insecticides to control EFSB, which increase production costs and pose risks to human health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Eggplant fruit and shoot borer, Leucinodes orbonalis Guenee (Lepidoptera: Pyralidae) is a destructive and first ranked insect pest constraint of eggplant production in almost eggplant growing areas of the world including Nepal (Mainali et al, 2013;Mainali, 2014). This insect has gained the potential status of pest due to larva's unique nature of feeding on monophagous diet aided by homing and tunneling behavior ultimately enables insects to face the challenges of chemical pesticides (Hanur et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial reduction in the productivity as well as the quality of the crop due to diseases, insects and other pests is the main basis that farmers are dispirited towards brinjal cultivation (Mainali et al, 2013). Measures like the use of resistant varieties, sex pheromones, cultural methods, use of physical as well as mechanical barriers, use of bio-pesticides, botanical pesticides, chemical methods can be practiced in the field to target the pest population level below the threshold level (Mainali, 2014). In Dhading district, major problem seen in the vegetable production is of insect's pests and diseases.…”
Section: Introductionmentioning
confidence: 99%